Analysis of HR Development Through Undergraduate Mandatory Policy of POLRI Investigators - Mustika, Dian; Suwandi, I Made (Jurnal Manajemen, 2022)
Basically to build a strong organizational culture takes a long time and gradually, each culture develops written and unwritten expectations about behaviour (rules and norms) that affect members of that culture. However, the organizational culture within the National Police is inseparable from the public's perception and perspective in obtaining information. Therefore, the achievements of Polri's work that have been conveyed to the public so far, both organizational and personal, have contributed to creating a positive or negative framework. In public opinion, it is possible that the ethics and philosophy of Polri as a form of organizational culture are very different from the daily practice of Polri's performance. As the performance of Polri investigators in solving problems, it is always under public scrutiny. As an organization with a clear and systematic hierarchy, PP No. 58 of 2010 concerning Amendment to Government Regulation Number 27 of 1983 concerning Implementation of the Criminal Procedure Code aims to get members of investigators who are able to clearly develop careers who work according to ethics and professionalism so as to improve the performance of investigators in carrying out their duties, functions and authorities. The development of human resources is the basic key to getting competent Polri Investigator personnel. For this reason, the development of competency-based human resources is a compulsory requirement for the National Police Investigating Unit. Thus, the presence of PP No. 58 of 2010 is able to provide more value in services to the community which of course has an impact on positive perceptions in the public.